A review of the application of variable geometry turbines to the downsized gasoline engine. (September 2015) - Tang, Huayin; Pennycott, Andrew; Akehurst, Sam; Brace, Chris J
Engine downsizing through turbocharging is a proven method of improving fuel economy by using a smaller engine operating at higher levels of specific engine load and higher efficiency. Turbocharging is more challenging for the gasoline engine than the diesel engine due to the higher variability in the flow rate of air and the higher exhaust gas temperature. Although the variable geometry turbine offers the potential for improving the low-end torque, lowering part-load fuel consumption and delivering a fast transient response on a downsized gasoline engine, the cost, durability and the limited allowable turbine inlet temperature on the currently available devices present challenges to widespread application. This article details the main operating principles and types of the variable geometry turbine, its potential to deliver performance improvements, implementation challenges on the gasoline engine and the measures available to alleviate those challenges. Of the available types of variable geometry turbine, the variable nozzle form has the highest efficiency over a wide flow range while the variable flow and sliding wall types have better reliability and lower cost. Using additional technologies such as the water-cooled exhaust manifold, specialist turbocharger materials, exhaust gas recirculation and novel combustion systems in combination with advanced control strategies will facilitate variable geometry turbine application and hence allow further downsizing of the gasoline engine.